ANALYSIS OF CONSUMER SATISFACTION LEVEL OF PT. PRIMA INDONESIA LOGISTICS - Elida Olivia Pangaribuan; Satria Tirtayasa; Hery Syahrial (SEAN Institute, 2022)
Based on the results of the analysis and processing of the questionnaire data it was concluded that for export activities there are two factors which according to the respondents are the top priority for improvement because they are not satisfactory, namely: The ability of Prima Indonesia Logistik employees to be responsive in dealing with complaints/problems arising from customers/service users ( with a suitability level of performance and importance of 80.83%), and fast and precise container loading and unloading operator services (export service time) (with a level of suitability of performance and interests of 84.68%). The percentage of satisfaction level for export service users is 13% very satisfactory, 46% satisfactory, 40% normal, 1% unsatisfactory, and 0% unsatisfactory. As for import activities, there are three factors which according to respondents are the top priority for improvement because they are not yet satisfactory, namely: Fast, precise and friendly service and always ready to help provided by Prima Indonesia Logistics employees (with a level of conformity of performance and interests of 75%); Prima Indonesia Logistics employees to be responsive in dealing with complaints/problems arising from customers/service users (with a suitability level of performance and interests of 78.33%); and Prima Indonesia Logistics officers provide clear and easy-to-understand information about import service procedures to customers (with an 80.75% level of suitability of performance and interest). The percentage of satisfaction level for users of imported services is 4% very satisfactory, 40% satisfactory, 42% normal, 13% unsatisfactory and 1% unsatisfactory.